Analisis Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) Terhadap Mutu Pelayanan di RS Mesuji Healthcare Center - Sri Agustina; Atikah Adyas; Yudhinanto CN; Noviansyah Noviansyah; Dian Utama Pratiwi Putri (Universitas Malahayati Lampung, 2024)
ABSTRACT Hospital information systems have the potential to improve individual health outcomes, improve health care provider performance, and minimize costs. Improving the quality of health services is influenced by four main aspects, including other people, processes, policies and infrastructure. One of these aspects is realized by a hospital information system which is designed to make hospital business processes responsive, efficient and effective. In this thesis